Vehicular road influence areas (2017)
Vehicle operation over paved and unpaved roads is an emission source that significantly contributes to air pollution. Emissions are derived from vehicle exhaust pipes and re-suspension of particulate matter generated by wind erosion and tire to road surface interactions. Environmental authorities require a methodology to evaluate road impact areas, which enable managers to initiate counter-measures, particularly under circumstances where historic meteorological and/or air quality data is unavailable. The present study describes an analytical and experimental work developed to establish a simplified methodology to estimate the area influenced by vehicular roads. AERMOD was chosen to model pollutant dispersion generated by two roads of common attributes (straight road over flat terrain) under the effects of several arbitrary chosen weather conditions. The resulting pollutant concentration vs. Distance curves collapsed into a single curve when concentration and distance were expressed as dimensionless numbers and this curve can be described by a beta distribution function. This result implied that average concentration at a given distance was proportional to emission intensity and that it showed minor sensitivity to meteorological conditions. Therefore, road influence was defined by the area adjacent to the road limited by distance at which the beta distribution function equaled the limiting value specified by the national air quality standard for the pollutant under consideration. © 2016 Elsevier Ltd